Analisis Faktor-faktor yang Memengaruhi Produktivitas Kelapa Sawit Rakyat Pola Swadaya di Desa Sungai Daka Kecamatan Sungai Laur Kabupaten Ketapang - Boby, Antonius; Fitrianti, Wanti; Oktoriana, Shenny (Universitas Galuh, 2025)
The purpose of this study is to analyze the factors that affect the productivity of smallholder oil palm in the self-help pattern in Sungai Daka Village, Sungai Laur District, Ketapang Regency. The method used in the study is a descriptive research method with a quantitative approach that is analyzed using a multiple linear regression model. The data sources used in this study are primary data and secondary data. The place of this research was taken deliberately (purposive), namely a self-help pattern oil palm plantation in Sungai Daka Village, Sungai Laur District, Ketapang Regency. The results of the study showed that simultaneously independent variables consisting of the number of plants, plant age, NPK fertilizer, organic fertilizer, pesticide and labor had a positive and significant influence on the productivity of self-help pattern oil palm in Sungai Daka Village, Sungai Laur District, Ketapang Regency. Meanwhile, the results of the partially tested data analysis concluded that NPK fertilizers and organic fertilizers had a real effect on the productivity of self-help pattern palm oil, while the number of plants, plant age, pesticides and labor had no real effect on the productivity of self-help pattern oil palm in Sungai Daka Village, Sungai Laur District, Ketapang Regency.